Understanding and addressing gender-based violence in Eswatini - Phumuzani Mpofu; Siphiwe Hlobsile Tfwala (International Review of Social Sciences Research)
The high prevalence of gender-based violence (GBV) in the kingdom of Eswatini is quiet saddening. Women and girl children become victims of GBV to the extent of losing their lives. Therefore, this article sought to find the causes of GBV, collaborative majors and guidelines to help reduce GBV. The paper employed a qualitative research design underpinned by a transformative paradigm as a framework for promoting preventive action toward social justice for marginalized populations. Participatory Action Learning Action Research (PALAR) was employed. A purposeful sample of traditional leaders, religious leaders, law enforcers, NGOs and public were selected. Data was obtained through individual interviews, focus group interviews and analyzed using the thematic analysis approach. Findings obtained revealed various causes of GBV: unequal power relations, socio-economic factors, weak legal and support systems. Study recommends that government in collaboration with stakeholders must establish educational programs and guidelines to fight GBV, improve psycho-social support, strengthen recreational systems, implement programs that focus on poverty alleviation and economic empowerment, decolonization of patriarchal cultural practices and develop awareness programs about issues faced by GBV survivors. Sexual offences domestic violence act (SODV) must be enforced by the law.